Rancangan Sistem Pengamanan Shelter DVOR di Bandar Udara Internasional Sam Ratulangi Manado - Rusman; Safitri, Rima (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
For supporting the fluency of flight safety operations, the facilities supporting of the flight safety needed to get maintenance, monitoring and safeguard, especially on equipment facilities flight aid navigation namely DVOR (Doppler Very High Frequency Omni Directional Range) at Sam Ratulangi International Airport in Manado that does not have adequate safeguards.The purpose of this design was to produce a security system of DVOR shelter in order the monitoring and safeguard DVOR shelter more effective. Method of this Design of security system using a motion sensor also called PIR (Passive Infrared Receiver) sensor which integrated with microcontroller. When the PIR sensor detects human motion, it will give the input to microcontroller for processing. The output of microcontroller will activate the alarm and showing the information on the LCD (Liquid Crystal Display) display and transmit commands to the module WAVECOM to make calls (speed dial) to any mobile security. After the security closes the call then the notification will appear in the form of SMS to turn off the alarm or keep to switch on the alarm until security arrived at the DVOR shelter location.The design of this security system was expected could help the security in monitoring from a long distance and improve the protection on the area around the DVOR shelter in order to monitor and minimize the action – of criminal acts in the area around DVOR shelter.Keywords: Design, Security System, Shelter, DVOR